PENGARUH DIMENSI TRUST, KEAMANAN DAN PRIVASI TERHADAP KEPERCAYAAN PENGGUNA UNTUK LAYANAN CLOUD COMPUTING BERBASIS SOFTWARE AS SERVICE - Haryani, Prita; Nugroho, Eko; Adhipta, Dani (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2015)
Cloud computing is one of latest innovation in the development of Internet-based computing technology. Cloud computing uses virtualization concepts that can be accessed via Internet, so can reduce the cost of Information Technology (IT) and facilitate IT service management. Service provided is multi-tenant so computing resources can be used together and adjusted to user needs (elasticity). Software as a Service (SaaS) is cloud computing services frequenly used. Security is a major problem in the development of cloud computing technology. Guarantee of security and privacy user data, it will raise trust of users to vendor.The study aims to analyze the factors can be effected trust of cloud computing user based on Software as a Service (SaaS). Samples that used are users who have been using cloud computing services based on Software as a Service (SaaS) more than three months. Instrument used is questionnaire and measured by scale Likert. There were 50 respondent in this study. The data analysis method used is Partial Least Square. Results of the study found that factors significantly affect user trust are ability, security and privacy of vendor.